2021
DOI: 10.3390/gels7040242
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Gelation for Synthesis of Surface-Modified Silica Aerogel Powders

Abstract: A spherical silica aerogel powder with hydrophobic surfaces displaying a water contact angle of 147° was synthesized from a water glass-in-hexane emulsion through ambient pressure drying. Water glass droplets containing acetic acid and ethyl alcohol were stabilized in n-hexane with a surfactant. Gelation was performed by heating the droplets, followed by solvent exchange and surface modification using a hexamethyldisilazane (HMDS)/n-hexane solution. The pH of the silicic acid solution was crucial in obtaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The FTIR spectra for treated powders are shown in Figure 3 . The bands that are typical of Si-O vibrations are visible in the recorded spectra and are identical to those that have been described in the literature [ 16 , 17 , 18 , 19 , 20 , 21 ]. Small bands at 560 cm −1 or 568 cm −1 may be attributed to the vibration of the Si-O-Zn bonds, whereas the main bands at 1273 cm −1 , 1080 cm −1 , 1114 cm −1 , 793 cm −1 , and 467 cm −1 are assigned to Si-O-Si bonds in networks and chains.…”
Section: Resultssupporting
confidence: 81%
“…The FTIR spectra for treated powders are shown in Figure 3 . The bands that are typical of Si-O vibrations are visible in the recorded spectra and are identical to those that have been described in the literature [ 16 , 17 , 18 , 19 , 20 , 21 ]. Small bands at 560 cm −1 or 568 cm −1 may be attributed to the vibration of the Si-O-Zn bonds, whereas the main bands at 1273 cm −1 , 1080 cm −1 , 1114 cm −1 , 793 cm −1 , and 467 cm −1 are assigned to Si-O-Si bonds in networks and chains.…”
Section: Resultssupporting
confidence: 81%
“…These results indicate that the fluorine-containing monomer of PI reduces the surface energy of materials as well as microstructure increases in surface roughness, therefore allowing the water droplets to slide away when the sample is slightly tilted. Based on the Wenzel’s model [ 48 , 49 , 50 ], the chemical composition and geometrical microstructure both influence the wettability, as the thermodynamic equilibrium (Equation (4)) shows: …”
Section: Resultsmentioning
confidence: 99%
“…This makes their direct use or hybridization with other materials difficult, which seriously limits the application of silica aerogel in many fields [18][19][20][21]. Moreover, the repeated modification process to transfer hydrophilicity to the hydrophobic surface of the silica aerogel monolith is tedious and requires an extremely long processing time [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the tiny volume of the silica aerogel powders, the modification and drying process is easier and faster, which effectively decreases the fabrication time. A few silica aerogel powders have been recently reported with various methods for rapid synthesis [22]. Pan et al reported a method to synthesize superhydrophobic (θ = 162 • ) aerogel powders at ambient pressure using a water-glass-based sol-gel method with a technological process of mechanical crushing and filtration [28].…”
Section: Introductionmentioning
confidence: 99%